1997
DOI: 10.1056/nejm199706123362402
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Based Radiotherapy to Inhibit Restenosis after Coronary Stenting

Abstract: In this preliminary, short-term study of patients with previous coronary restenosis, coronary stenting followed by catheter-based intracoronary radiotherapy substantially reduced the rate of subsequent restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
371
1
24

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 893 publications
(402 citation statements)
references
References 27 publications
6
371
1
24
Order By: Relevance
“…Many clinical studies of intracoronary radiation therapy have reported successful reduction of restenosis (Condado et al, 1997;Teirstein et al, 1997;King et al, 1998;Waksman et al, 2000). The main mechanism of radiation is to inhibit the proliferative response of VSMCs at the site of injury .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical studies of intracoronary radiation therapy have reported successful reduction of restenosis (Condado et al, 1997;Teirstein et al, 1997;King et al, 1998;Waksman et al, 2000). The main mechanism of radiation is to inhibit the proliferative response of VSMCs at the site of injury .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inhibition of vascular smooth muscle cell (VSMC) proliferation, which constitutes the major portion of the neointima, is the main target of therapy in restenosis prevention. Accordingly, intracoronary radiation therapy (or coronary brachytherapy), is one of the most promising anti-restenotic modalities due to its antiproliferative, proapoptotic effects along with cell cycle arrest (Teirstein et al, 1997). However, VSMCs are relatively resistant to radiation (Brenner et al, 1996) compared with other cells and intracoronary radiation has been shown to have some adverse side effects at high doses such as late thrombosis and coronary artery aneurysm (Condado et al, 1999;Farb et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…O estudo SCRIPPS (Catheter-Based Radiotherapy to Inhibit Restenosis After Coronary Stenting) comparou o uso da radiação gama com o placebo em lesões reestenóti-cas, mostrando uma taxa de reestenose de 17% versus 54% em seis meses (p=0,01) e de 33% versus 64% em três anos (p<0,05) 43,44 . Portanto, apesar da radiação gama ocasionar uma redução de 69% na taxa de reestenose em seis meses e esta diminuir para 48% em três anos, ainda assim a redução da taxa de reestenose em três anos permaneceu significativa, o que demonstra os efeitos benéficos da braquiterapia a longo prazo.…”
Section: Tabela VII -Resultados Do Estudo Arts Em 12 Mesesunclassified
“…Intracoronary radiation (brachytherapy) appears promising, but there are serious concerns about its long-term safety. 10,11 Antiplatelet therapy by means of agents with rapid onset of action have had a sizeable impact on the incidence of early lumen loss, caused by increased platelet aggregation immediately following stent implantation. [12][13][14] However, later lumen loss, attributable in large part to neointimal hyperplasia and thrombus formation, has proved more problematic.…”
Section: Introductionmentioning
confidence: 99%